La vivencia sexual del maestro… otra manera de transitar y de habitar el cuerpo (2011)
ABSTRACT: The results of this research show that the teachers manifested attitudes with erotophiliac tendencies, understood as their predisposition to evaluate, perceive, feel and act in a favorable way when asked about different sexual stimuli mentioned in the research. The teachers demonstrated a communicative and expressive vision of the body that went beyond appearance and body image and allowed them to relate with others. This vision corresponds with their definition of sexual autonomy, centered in decisions about their own bodies, values such as responsibility, self-esteem and freedom, and the livelihood of pleasure and assertive communication. In this sense, a significant piece of data is the extension of the map of erogenous zones which the teachers described as important to their level of enjoyment and satisfaction when touching and being touched. Gender had little bearing on this data, a point which validates the fact that flexibility of gender roles in the attitudes of the teachers generates equality and improves their human interaction. Satisfying sexual practices are related to favorable attitudes. In this way, positive sexual experience is an indicator that favors institutional sexual education projects as a pedagogical matter and at the same time promotes quality of life seen in indicators such as health, pleasurable erotic-affective relations, personal empowerment and the strengthening of social and individual values.